4,6-Dichloro-2-{[(E)-(3-{[(E)-3,5-dichloro-2-hydroxybenzylidene]amino}-2,2-dimethylpropyl)imino]methyl}phenol - Kargar, Hadi (International Union of Crystallography, 2011)
In the title compound, C(19)H(18)Cl(4)N(2)O(2), a potential tetradentate Schiff base ligand, the dihedral angle between the two benzene rings is 48.01 (10)°. The configuration about the two C=N bonds is E and two intramolecular O—H⋯N hydrogen bonds make S(6) ring motifs. In the crystal, molecules are linked along the b axis via intermolecular C—H⋯Cl interactions. The crystal structure is further stabilized by an intermolecular π–π interaction [centroid–centroid distance = 3.5744 (12) Å].